Impaired Responsiveness to the Platelet P2Y12 Receptor Antagonist Clopidogrel in Patients With Type 2 Diabetes and Coronary Artery Disease - Angiolillo, Dominick J.; Jakubowski, Joseph A.; Ferreiro, José Luis; Tello-Montoliu, Antonio; Rollini, Fabiana; Franchi, Francesco; Ueno, Masafumi; Darlington, Andrew; Desai, Bhaloo; Moser, Brian A.; Sugidachi, Atsuhiro; Guzman, Luis A.; et al. (Journal of the American College of Cardiology, 2014)
Several studies have shown that patients with diabetes mellitus (DM) exhibit an impaired response to clopidogrel. This may contribute to their increased risk of recurrent atherothrombotic events, despite the use of dual-antiplatelet therapy. The mechanisms for impaired clopidogrel response in DM patients have not been fully elucidated. The aim of this study was to explore the mechanisms for impaired clopidogrel-mediated platelet inhibition in patients with DM using a comprehensive methodological approach embracing both pharmacokinetic (PK) and pharmacodynamic (PD) assessments as well as ex vivo and in vitro investigations. Patients (DM, n = 30; non-DM, n = 30) with stable coronary artery disease taking aspirin 81 mg/day and P2Y12 antagonist naive were enrolled. Blood was collected before and at various times (0.5, 1, 2, 4, 6, and 24 h) after a 600-mg loading dose of clopidogrel. PD assessments included vasodilator-stimulated phosphoprotein, light transmission aggregometry, and VerifyNow P2Y12 ex vivo, before and after dosing and following in vitro incubation with escalating concentrations (1, 3, and 10 μM) of clopidogrel’s active metabolite (Clop-AM). Exposure to Clop-AM was also determined. PD assessments consistently showed that during the overall 24-h study time course, residual platelet reactivity was higher in DM patients compared with non-DM patients. In vitro incubation with Clop-AM revealed altered functional status of the P2Y12 signaling pathway in DM platelets as measured by vasodilator-stimulated phosphoprotein, but not with other PD assays. Clop-AM exposure was ∼40% lower in DM patients than in non-DM patients. The present study suggests that among DM patients, impaired P2Y12 inhibition mediated by clopidogrel is largely attributable to attenuation of clopidogrel’s PK profile. This is characterized by lower plasma levels of Clop-AM over the sampling time course in DM patients compared with non-DM patients and only modestly attributed to altered functional status of the P2Y12 signaling pathway.